Building and managing microservices with Kubernetes and Istio (LiveLessons (Boston, Massachusetts), 2021)
6+ Hours of Video Instruction Learn the most efficient way to manage and run Microservices in Kubernetes and Istio. Overview Microservices are the new development model for running complex applications. Building and Managing Microservices with Kubernetes and Istio LiveLessons will cover the topics you will need to run successful Microservices in Kubernetes and Istio. Building and Managing Microservices with Kubernetes and Istio LiveLessons starts with an overview of Microservices and why it is the right choice to run complex applications. The course will then discuss how to automatically implement Microservices using Kubernetes, a procedure that starts with source files in Git, before exploring topics of container images and how to build them efficiently. Lastly, it will also cover how to apply decoupling in Kubernetes for full implementation of automated and orchestrated Microservice environment. Instructor Sander van Vugt uses hands-on-labs to give you a deeper understanding of the topics covered in the course. About the Instructor Sander van Vugt has many years of experience working with, writing about, and teaching Linux and Open Source topics. He is the author of the best-selling Red Hat RHCSA Cert Guide and the Red Hat RHCSA Complete Video Course along with many other titles on topics that include RHCE, Bash, Kubernetes, Ansible and more. Sander also works as a Linux instructor, teaching on-site and on-line classes for customers around the world. Topics include: Understanding Microservices Using Git Containers QuickStart Understanding Container Orchestration and Service Mesh Getting Started with Kubernetes Creating Container-based Microservices in Kubernetes Getting Started with Istio Service Mesh Managing Microservices with Istio Service Mesh Skill Level Beginner to Intermediate Learn How To Manage source code for microservices Build custom container images Use Kubernetes technology to manage Microservices Use Service Mesh Who Should Take This Course This course is for anyone who wants to learn how to move from traditional applications that are installed on a server platform to orchestrated containers in a Microservices environment. The course is for developers and DevOps engineers who want to know what happens after the code is written, as well as administrators responsible for implementing the Microservices infrastructure. Course Requirements A computer with a recent operating system and at least 4GB RAM and 20GB available disk space About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.